The Development and Validation of the Bergen–Yale Sex Addiction Scale With a Large National Sample - Andreassen, Cecilie S.; Pallesen, Ståle; Griffiths, Mark D.; Torsheim, Torbjørn; Sinha, Rajita (Frontiers in Psychology, 2018)
The view that problematic excessive sexual behavior (‘sex addiction’) is a form of behavioral addiction has gained more credence in recent years, but there is still considerable controversy regarding operationalization of the concept. Furthermore, most previous studies have relied on small clinical samples. The present study presents a new method for assessing sex addiction––the Bergen–Yale Sex Addiction Scale (BYSAS)––based on established addiction components (i.e., salience/craving, mood modification, tolerance, withdrawal, conflict/problems, and relapse/loss of control). Using a cross-sectional survey, the BYSAS was administered to a broad national sample of 23,533 Norwegian adults (aged 16–88 years; mean [± SD] age = 35.8 ± 13.3 years), together with validated measures of the Big Five personality traits, narcissism, self-esteem, and a measure of sexual addictive behavior. Both an exploratory and a confirmatory factor analysis (RMSEA = 0.046, CFI = 0.998, TLI = 0.996) supported a one-factor solution, although a local dependence between two items (Items 1 and 2) was detected. Furthermore, the scale had good internal consistency (Cronbach’s = 0.83). The BYSAS correlated significantly with the reference scale (r = 0.52), and demonstrated similar patterns of convergent and discriminant validity. The BYSAS was positively related to extroversion, neuroticism, intellect/imagination, and narcissism, and negatively related to conscientiousness, agreeableness, and self-esteem. High scores on the BYSAS were more prevalent among those who were men, single, of younger age, and with higher education. The BYSAS is a brief, and psychometrically reliable and valid measure for assessing sex addiction. However, further validation of the BYSAS is needed in other countries and contexts.